Teaching “The Nature Of Public International Law” To LL.M. Students - Yeremyan, L. A. (Մանկավարժ հրատ․)
The main aim of elaboration of a study course titled “The Nature of Public International Law” is promoting teaching of International Law in Higher Educational Institutions among all LL.M. students regardless of the chosen specialization. Teaching such a study course also aims at developing and enhancing the analytical skills of the students, argumentation competence and other professional competences and skills, as well as at facilitating the accurate and efficient implementation of International law in national legal system. “Միջազգային հանրային իրավունքի բնույթը” վերտառությամբ ուսումնական ծրագրի մշակման հիմնական նպատակն է խթանել միջազգային հանրային իրավունքի (ՄՀԻ) դասավանդումը ԲՈՒՀ-երում իրավագիտության ոլորտում մագիստրատուրայի բոլոր ուսանողների շրջանում` անկախ մասնագիտացումից: Ուսումնական ծրագիրն ունի նաև խնդիր զարգացնել ուսանողների վերլուծական, փաստարկներ բերելու և այլ մասնագիտական կարողություններն ու հմտությունները, ինչպես նաև խթանել ներպետական իրավունքում միջազգային իրավունքի ճշգրիտ իմպլեմենտացիայի իրականացմանը: Основной целью учебного курса “Природа международного публичного права” является дальнейшее развитие в ВУЗ-ах преподавания международного публичного права всем учащимся в магистратуре по направлению “Юриспруденция”, не зависимо от выбранной ими узкой специальности. Одной из задач данной учебной программы также является способствование развитию у студентов аналитических компетенций, компетенций аргументации и других профессиональные компетенций и навыков, а также способствовать аккуратной и правильной имплементации норм международного права в национальное законодательство.
Keywords: Public International Law; Teaching methodology